M2C and M6C carbide precipitation in Ni-Mo-Cr based superalloys containing silicon. (15th December 2016) - Jiang, Li; Zhang, Wen-Zhu; Xu, Zhou-Feng; Huang, He-Fei; Ye, Xiang-Xi; Leng, Bin; Yan, Long; Li, Zhi-Jun; Zhou, Xing-Tai
Abstract: The effect of silicon additions on the primary carbides and second grain boundary carbides has been investigated in as-cast and wrought Ni-Mo-Cr based alloys, respectively. With the increase of Si content in the as-cast alloys, the lamellar M2 C eutectic carbides at grain boundaries were replaced by skeleton-shape M6 C eutectic carbides in interdendritic regions. The wrought alloys with different Si contents were thermal exposed at 750 °C for 1, 500 and 2000 h, respectively. It can be observed that the initial M2 C carbides formed at grain boundaries were replaced by M6 C carbides in the low-Si alloys (0.051 and 0.188 wt.%) with the increase of exposure time. Only M6 C carbides precipitated at grain boundaries in the alloy with 0.562 wt.% Si, which coarsened during the thermal exposure. Similar trends also existed in the high-Si alloy except an abnormal formation of M2 C carbides after 2000 h' exposure. The effect of Si additions on the types of carbides was attributed to competitive nucleation between M2 C carbides and M6 C carbides based on classical nucleation theory. Graphical abstract: Highlights: The increase of Si content inhibits M2 C carbides and promotes M6 C carbides. High nucleation rate of M6 C carbides with Si supports their preferential formation. Large account of M6 C carbides lead to the low matrix Si content in highest-Si alloy.